2018
DOI: 10.1111/all.13479
|View full text |Cite
|
Sign up to set email alerts
|

Gata3 hypermethylation and Foxp3 hypomethylation are associated with sustained protection and bystander effect following epicutaneous immunotherapy in peanut‐sensitized mice

Abstract: Our study demonstrates that EPIT leads to a unique and stable epigenetic signature in specific T-cell compartments with downregulation of Th2 key regulators and upregulation of Treg transcription factors, likely explaining the sustainability of protection and the observed bystander effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 53 publications
2
59
0
Order By: Relevance
“…In the present study, we demonstrated that AIT differentially modifies the activation and function of several Treg subsets. AIT in vivo increased subsets of allergen‐specific Treg cells with distinct phenotypes, and the mechanisms of action include the CD4 + CD25 + CD127 − FOXP3 + nTreg and the CD4 + IL‐10‐secreting Tr1 cells . In addition to changes in allergen‐specific Treg cells, we observed that in 9 out of 12 patients, overall IL‐10 + Tr1 cells also increased during AIT, which is concordant with the previous data reported by others …”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we demonstrated that AIT differentially modifies the activation and function of several Treg subsets. AIT in vivo increased subsets of allergen‐specific Treg cells with distinct phenotypes, and the mechanisms of action include the CD4 + CD25 + CD127 − FOXP3 + nTreg and the CD4 + IL‐10‐secreting Tr1 cells . In addition to changes in allergen‐specific Treg cells, we observed that in 9 out of 12 patients, overall IL‐10 + Tr1 cells also increased during AIT, which is concordant with the previous data reported by others …”
Section: Discussionsupporting
confidence: 91%
“…82 In the same context, Foxp3 promoter hypomethylation in CD62L Tregs and GATA3 promoter hypermethylation in Th2 cells were associated with sustained protection in mice. 83 More recently, it was shown that while both Langerhans cells and CD11b+ cDC2s acquire and present topical antigen to T cells, the IRF-4-dependent cDC2s are required for T-cell priming and LAP+ Treg expansion. 84 In contrast to epicutaneous immunotherapy, epicutaneous sensitization resulting in food allergy can occur when the skin barrier is damaged.…”
Section: Mechanistic Insights From Mouse Models On How To Treat Foomentioning
confidence: 99%
“…Similarly, recently, we have shown in a mouse model of epicutaneous immunotherapy for peanut allergy that Foxp3 methylation was reduced on successful epicutaneous immunotherapy, whereas methylation of the T H 2 key transcription factor Gata3 was specifically increased in splenic CD4 1 IL-4 1 T cells. 19 In contrast, oral immunotherapy induced only demethylation of Foxp3 but not methylation of Gata3, suggesting that the latter might be important to maintain the level of sustained unresponsiveness and protection against sensitization to a second allergen observed in epicutaneous immunotherapy.…”
Section: Dna Methylation As a Biomarker For Treatment And Immunotherapymentioning
confidence: 95%
“…Although a major criticism of DNA methylation analyses has been that changes will only reflect variations in proportions of the analyzed cell populations, recent results have also shown that not only are cell proportions changed but also the epigenomic landscape is modified in specific cell populations. 10,19 Nonetheless, EWASs have great potential for explaining phenotypic variability, as exemplified by a study on DNA methylation levels associated with serum IgE levels, which showed a 10-fold greater capacity of genome-wide DNA methylation patterns to explain the observed variability in IgE concentrations compared with genetic variation. 20 EWASs might not only deepen our understanding of the underlying disease etiology by pointing to disease-relevant pathways, such as the T H 1/T H 2 pathway 21 and other immunologically relevant pathways in patients with cow's milk allergy 22 but could also provide a multitude of other target genes that need to be further investigated in functional studies, including transcription factors, mitochondrial proteins, and proteins involved in T-cell maturation or oxidative stress.…”
Section: Dna Methylationmentioning
confidence: 99%